Towards UAV-based Land Tenure Data Acquisition in RwandaNeeds Assessment and Technology Response - Stöcker C. (null, 2020)
This study sheds light on the needs assessment and design process of UAV-based data acquisition workflows and reveals results of data collection activities and initial UAV test flights in Rwanda. Insights into operational challenges and data quality measures are presented. The paper concludes that the tool of UAV-based data collection seems to offer an answer to the majority of the expressed needs which were assessed with the NGT method. However, the realization of the test flights also reveals three specific challenges that have to be addressed before UAVs can be used for large scale mapping in Rwanda.